Indeks Szeged dari Berbagai Representasi Graf dari Grup Bilangan Bulat Modulo : Szeged Index of Various Graph Representations of the Modulo Integer Group - Muthahira Qalbi D; Fariz Maulana (Semeton Mathematics Journal, 2026)
The Szeged index is a topological index used to analyze graph structures based on vertex distances. This article reviews the application of the Szeged index on three types of graphs constructed from modular integer groups, namely power graphs, non-coprime graphs, and prime coprime graphs. Each graph has a different connection rule, resulting in variations in the Szeged index values. This study aims to compare the results across the graph types and examine how the group structure influences the index values.